Cardiac Amyloidosis: Clinical Features, Pathogenesis, Diagnosis, and Treatment - Asuman ARGON; Deniz NART; Funda YILMAZ BARBET (Federation of Turkish Pathology Societies, 2024)
Cardiac amyloidosis is a type of amyloidosis that deserves special attention as organ involvement significantly worsens the prognosis. Cardiac amyloidosis can be grouped under three main headings: immunoglobulin light chain (AL) amyloidosis that is dependent on amyloidogenic monoclonal light chain production; hereditary Transthyretin (TTR) amyloidosis that results from accumulation of mutated TTR; and wild-type (non-hereditary) TTR amyloidosis formerly known as senile amyloidosis. Although all three types cause morbidity and mortality due to severe heart failure when untreated, they contain differences in their pathogenesis, clinical findings, and treatment. In this article, the clinical features, pathogenesis, diagnosis, and treatment methods of cardiac amyloidosis will be explained with an overview, and an awareness will be raised in the diagnosis of this disease.